HUBUNGAN KECERDASAN EMOSIONAL DENGAN INTERAKSI SOSIAL SISWA KELAS V UPT SD INPRES 12/79 LONRAE KECAMATAN TANETE RIATTANG TIMUR KABUPATEN BONE - Sri Wahyuni; Rosmalah Rosmalah; Makmur Nurdin; Muhammad Amran (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
; This study uses a quantitative approach with the type of correlation which aims to determine the relationship of emotional intelligence with the social interaction in class V UPT SD Inpres 12/79 Lonrae Kecamatan Tanete Riattang Timur Kabupaten Bone. The population in this study were 48 students, namely class VA as many as 24 and class VB as many as 24, while the sample was the entire population of 48 students. The sampling technique used was saturated sampling technique. The research data were obtained by using a questionnaire. The data analysis technique was carried out by descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, students' emotional intelligence has an average of 72.33 and a percentage of 79.34% in the good category and the students' social interactions have an average of 107.77 and a percentage of 79.79% in the very good category. Then, based on the results of inferential statistical analysis, the tcount (9.44498) is greater (>) the ttable value (1.67866) at a significant level of 5%. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship of emotional intelligence with the social interaction in class V UPT SD Inpres 12/79 Lonrae Kecamatan Tanete Riattang Timur Kabupaten Bone.